HUBUNGAN KESEJAHTERAAN PSIKOLOGIS DENGAN ASPIRASI KARIR SISWA SMA DI BANDAR LAMPUNG - citra abriani maharani; Yohana Oktarina (Program Studi Psikologi Universitas Malahayati, 2020)
ABSTRACT : RELATIONSHIP OF PSYCHOLOGICAL WELL-BEING AND CAREER ASPIRATION AMONG HIGH SCHOOL STUDENTS IN BANDAR LAMPUNG Psychological well-being is the full achievement of a person's psychological potential which makes an individual able to function properly in carrying out all duties and responsibilities as an individual. This study aims to determine the relationship between the level of psychological well-being and career aspirations of high school students in Bandar Lampung. The sample in this study involved 88 high school students in Bandarlampung who were selected using cluster sampling. This research method is quantitative with a correlational research design. Measurement tools used in this study are a scale of psychological well-being and career aspirations. The analysis technique used in this research is the product moment correlation. The results showed that there is a strong relationship between psychological well-being and career aspirations of high school students in Bandarlampung. Keywords: Psychological Well-being, Career Aspirations, High School Student Kesejahteraan Psikologis merupakan pencapaian penuh dari potensi psikologis seseorang yang membuat individu mampu berfungsi dengan baik dalam mengerjakan segala tugas dan tanggung jawab sebagai individu. Penelitian ini bertujuan untuk mengetahui secara mendalam hubungan antara tingkat kesejahteraan psikologis terhadap aspirasi karir pada siswa SMA di Bandar Lampung. Sampel dalam penelitian ini melibatkan siswa SMA di Bandarlampung sebanyak 88 orang yang dipilih dengan menggunakan cluster sampling. Metode penelitian ini adalah kuantitatif dengan desain penelitian korelasional.. Alat pengukuran yang digunakan dalam penelitian ini berupa angket skala kesejahteraan psikologis dan skala aspirasi karir. Teknik analisis yang digunakan dalam penelitian ini adalah crelasion product moment. Hasil penelitian menunjukkan bahwa terdapat hubungan yang kuat antara kesejahteraan psikologis terhadap aspirasi karir siswa SMA di Bandarlampung. Kata kunci: Kesejahteraan Psikologis, Aspirasi Karir, Siswa SMA